GENETICS AND NEUROPATHOLOGY OF HUNTINGTON’S DISEASE - Reiner, Anton (Int Rev Neurobiol, 2011)
Huntington’s disease (HD) is an autosomal dominant progressive neurodegenerative disorder that prominently affects the basal ganglia, leading to affective, cognitive, behavioral and motor decline. The basis of HD is a CAG repeat expansion to >35 CAG in a gene that codes for a ubiquitous protein known as huntingtin, resulting in an expanded N-terminal polyglutamine tract. The size of the expansion is correlated with disease severity, with increasing CAG accelerating the age of onset. A variety of possibilities have been proposed as to the mechanism by which the mutation causes preferential injury to the basal ganglia. The present chapter provides a basic overview of the genetics and pathology of HD.